COVID-19: Pathogenesis, Diagnosis, and Treatment - Hasan Waliyurrahim; Rina Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Coronavirus disease 2019 (COVID-19) is a disease of the respiratory system that spreads rapidly throughout the world with significant mortality and morbidity rate. This literature review aims to provide related information, so as to find out how SARS-CoV-2 is transmitted, the latest control, prevention, and treatment strategies. We searched from online databases and used review articles, research, guidelines from professional organizations, such as Ministry of Health Republic of Indonesia. SARS-CoV-2 spreads rapidly through droplets and attacks the respiratory system by binding to the ACE-2 receptor. This virus spreads from symptomatic or asymptomatic people. Diagnostic accuracy can be improved by combining clinical evidence with results from CT-scans and RT-PCR. Management for COVID-19 patients is carried out based on severity. Understanding pathogenesis can help determine the next step in treatment and prevention of COVID-19.